PENGEMBANGAN MEDIA PEMBELAJARAN BIG BOOK PANCASILA “BIOPAN” UNTUK PENINGKATAN PEMAHAMAN NILAI PANCASILA PADA SISWA KELAS 1 - Indriana , Sugati; Yuni Alfiyah, Hanik; Ghozali, Solchan (ILJ: Islamic Learning Journal, 2024)
The present study aimed to develop the "BIOPAN" Pancasila Big Book learning media for Civics education in grade 1 of MI/SD schools to facilitate the delivery of the learning material for teachers. The research employed a development research (R&D) approach utilizing the ADDIE model, comprising of three stages: analysis, design, and development. The validity of the developed media was evaluated by two validators, assessing aspects of media, design, and material. The results revealed that the "BIOPAN" Big Book learning media was highly valid with a score of 89.61%. Thus, the effectiveness and practicality of the Big Book “BIOPAN” learning media can be tested so that it can be utilized for Pancasila learning in the PPKn subject.